Development of Subject Gateways: A Status Update - Kanetkar, Jayashree (DESIDOC Journal of Library & Information Technology, 2014)
<!– P margin-bottom: 0.21cm; direction: ltr; color: rgb(0, 0, 10); line-height: 115%; widows: 2; orphans: 2; P.western font-family: "Calibri",serif; font-size: 11pt; P.cjk font-family: "WenQuanYi Micro Hei"; font-size: 11pt; P.ctl font-family: "Calibri"; font-size: 11pt; A:link color: rgb(0, 0, 255); –> Development of the internet and the world wide web has made impact on the libraries like never before. Ownership of documents has given way to access, forcing a rethinking of the functions and services to be performed by libraries for providing the specific documents/information needed by users from the ocean of digital resources. One such service designed to provide access to evaluated, and selected information resources pertaining to a particular subject field is the subject gateway service. This article traces the development of subject gateways from 1999 till 2013 and critically studies the longest surviving subject gateways. It shows that the most critical feature expected of a subject gateway, i.e., evaluation of resources prior to selection, is missing in majority of the subject gateways. http://dx.doi.org/10.14429/djlit.34.5807